Impact of Repositioning Duration on Cardiorespiratory Status in Ventilated Patients - Bagus Ananta Tanujiarso; Dewi Handayani (Indonesian Journal of Global Health Research, 2026)
Immobilization in mechanically ventilated ICU patients frequently alters cardiorespiratory stability. While regular repositioning is standard nursing care to prevent complications, the optimal duration tolerated before hemodynamic shifts occur remains poorly characterized. Objective to analyze the effect of repositioning and its duration on hemodynamic and respiratory status among mechanically ventilated patients in the Intensive Care Unit. A pre-experimental study with a one-group pretest-posttest design was conducted in the ICU of Telogorejo Hospital, Semarang. A total of 20 mechanically ventilated patients were recruited via accidental sampling. Physiological parameters heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), oxygen saturation (SpO2), respiratory rate (RR), and tidal volume (TV) were measured before and immediately after repositioning until physiological changes occurred (maximum duration 2 hours). Data were analyzed using paired comparative tests and correlation analyses. Repositioning significantly altered all measured cardiorespiratory parameters (p<0.05): HR increased from 89.00 ± 15.45 to 103.00 ± 18.79 bpm (p = 0.003), SBP from 119.00 ± 26.65 to 129.00 ± 23.49 mmHg (p = 0.014), DBP from 63.00 ± 15.68 to 67.00 ± 16.10 mmHg (p = 0.006), SpO2 from 99.00 ± 0.92% to 100.00 ± 0.59% (p = 0.035), RR from 16.00 ± 4.55 to 27.00 ± 9.01 breaths/min (p = 0.000), and TV from 441.00 ± 64.97 to 476.00 ± 76.77 mL (p = 0.002). The mean duration before parameter changes was 46.75 ± 10.42 minutes. Repositioning duration showed a significant moderate positive correlation only with changes in diastolic blood pressure (r = 0.602, p = 0.005), while changes in other parameters were not significantly correlated with duration (p > 0.05). Repositioning induces significant physiological responses in mechanically ventilated patients, with hemodynamic shifts emerging at an average of 47 minutes. Critical care nurses should adopt individualized repositioning intervals tailored to patient stability rather than relying solely on rigid two-hour protocols.